Products of interaction of substituted 5-aminopyrazoles with α -haloketones as potential pharmaceutical agents - Tkachenko, Pavlo; Tkachenko, Olena; Netosova, Krystyna; Borisov, Oleksandr; Zhuravel, Iryna (ScienceRise: Pharmaceutical Science, 2017)
Aim. Optimization of reaction of substituted 5-aminopyrazoles with a-haloketones to form annealed 2,6,7-trisubstituted 1H-imidazo[1,2-b]pyrazoles. Materials and methods of research. The methods of organic synthesis, instrumental methods of organic compound analysis were used. Results. A scheme for the synthesis of 2,6,7-trisubstituted 1H-imidazo[1,2-b]pyrazoles by the interaction of 5-amino-4-arylsulfonyl-3-methylthiopyrazoles 1a-b with chloroacetone, phenacyl bromide and 2-chlorocyclohexanone was developed. In contrast to the previously described interaction of substituted 5-aminopyrazoles with chloro (N-aryl) acetamides proceeding exclusively with the release of N1-alkylation products, in this reaction a mixture of N1- and N2-isomeric alkylation products is formed. The ratio of isomers depends on the nature of the reagents and, according to the 1H NMR-spectroscopy, is about 60:40 %.The developed technique allows with one of the synthetic procedure to carry out N1-alkylation of 5-aminopyrazoles 1a-b and the cyclization of products 2 in imidazo[1,2-b]pyrazoles 4a-c without isolating the N2-alkylation product. The purity of the obtained compounds is proved chromatographically, the structure is confirmed by the data of 1H NMR-spectroscopy. Conclusions. Optimized reaction of substituted 5-aminopyrazoles with a-haloketones to form annealed 2,6,7-trisubstituted 1H-imidazo[1,2-b]pyrazoles for targeted synthesis of the novel agents for the pharmaceutical practice